Contextual Learning and Hydrocarbon Conceptual Mastery in Integrated Islamic High School - Renda Suri Pratimi (ITScience (Information Technology and Science), 2026)
Hydrocarbon concepts represent a cornerstone of organic chemistry, yet mastering them remains challenging for many high school students due to their abstract nature and dependence on multi-level representations. In Indonesian secondary education, where chemistry is perceived as daunting due to limited hands-on experience and heavy reliance on lectures, this difficulty persists across institutions such as SMA IT Nurul Fikri, reflecting national curriculum standards aligned with KKM benchmarks. Traditional teaching methods often fail to connect theory with practice, leading to widespread misconceptions that hinder deeper understanding. To assess this issue, a quantitative approach with a pre-experimental one-group pretest–posttest design. The research participants were 15 science students from Nurul Fikri Selong Integrated Islamic High School. Qualitative coding analyzed responses for themes of superficiality, partial insight, and total confusion, drawing on established frameworks in the chemical education literature. Pretest results revealed a critical deficit: an average score of 49.67/100, far below the 70 KKM threshold, indicating systemic gaps in conceptual retention. Of participants, 50% offered rephrased or off-topic replies, indicating shallow engagement; 10% grasped the basics but struggled with application; and 40% showed no familiarity with fundamentals. These trends mirror prior Indonesian studies showing error rates of up to 50% in differentiating hydrocarbon types via rote learning, resulting in flawed predictions for processes such as halogenation. Conclusively, the findings advocate shifting toward interactive pedagogies, such as inquiry-based activities and collaborative dialogues, to cultivate metacognition and move from passive absorption to active problem-solving. Future implementations could integrate digital simulations for experiential insights, potentially elevating performance beyond mere recall.